PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Bintang Zaura; Muhammmad Arifin; Syahjuzar Syahjuzar (Jurnal Peluang, 2020)
One effort to enhance human resources is through learning mathematics. Achieving the objectives of learning mathematics requires creative thinking skills. However, several research results clearly showed that students' creative thinking abilities remained relatively low. Mathematics Problem Based Learning learning model is one model that can construct students' creative thinking skills and it can be applied to quadrilateral material. The research problem of this study is whether there is an increase in students' creative thinking skills after experiencing Problem Based Learning model on quadrilateral material in Year 7 of junior high school. The approach used was a quantitative approach with true experimental design, one-group pretest and posttest. The research population was all students of class VII-1 (28 people). Data collection was done by a test. The data analysis showed that tcount and or tcount  ttable. Thus, it can be concluded that the Problem based learning model can improve the mathematical creative thinking skills Year 7 students at SMP Negeri 1 Darul Makmur Nagan Raya.